ESTUDIO DEL RATING Y SU EFECTO EN EL MERCADO PUBLICITARIO CON RADIODIFUSORAS DEL CANTÓN QUEVEDO, AÑO 2022 - Peña Parraga, Lessly Madeleynne (2022)
The main objective of this research project was to carry out a study of the rating and advertising market with radio stations in the Quevedo canton in 2022, for which it sought to identify the advertising supply and demand maintained by the radio stations in the canton, and the importance of the rating in the labor market of broadcasters. A rating measurement system was proposed as a business model with the radio stations of Quevedo, as a feasible and beneficial project for the labor market. The methodology used was qualitative exploratory research, of the inductive-deductive type, explaining the nature of the phenomenon to carry out the proposals for action on the reality described; through the use of the interview as a data collection instrument, to a non-probabilistic sample of eleven radio broadcasters and nine representatives of private companies in Quevedo. Among the most relevant results, it was obtained that rating studies benefit the labor market, since they allow private companies to program their advertisements at times of greater scope, which increases the economic income of both parties.